MUTU BRIKET ARANG CAMPURAN LIMBAH PENGOLAHAN KOLANG KALING (Arenga pinnata) DAN LIMBAH PENGOLAHAN ARANG KAYU ALABAN (Vitex pubescens) - Yuniarti, Yuniarti; Thamrin, Gurti A. R.; Kurdiansyah, Kurdiansyah; Yazan, Syaiful; Sutiya, Budi (Jurnal Hutan Tropis, 2025)
This study aims to analyze the quality of charcoal briquettes produced from a mixture of kolang-kaling processing waste and alaban wood charcoal processing waste. The parameters assessed include moisture content, density, ash content, volatile matter, fixed carbon, and calorific value. The research method involved sample preparation and characterization of biobriquettes using the Indonesian National Standard (SNI) 06-3730-1995, which includes tests for moisture content, density, ash content, volatile matter, fixed carbon, and calorific value. The carbonization process was conducted using a simple drum kiln, and the briquettes were molded using 10% tapioca starch as a binder. Five composition treatments were applied: (A) 100% kolang-kaling processing waste charcoal; (B) 75% kolang-kaling processing waste charcoal + 25% alaban wood charcoal; (C) 50% kolang-kaling processing waste charcoal + 50% alaban wood charcoal; (D) 25% kolang-kaling processing waste charcoal + 75% alaban wood charcoal; (E) 100% alaban wood charcoal. Each treatment was replicated three times. The briquettes were shaped using a manual press mold. The results showed that the briquettes had physical characteristics with a moisture content ranging from 5.490% to 11.641% and a density between 0.835–1.070 g/cm³. The chemical characteristics included an ash content of 1.497%–16.197%, volatile matter of 40.593%–47.177%, and a calorific value between 3,781.69–5,708.92 cal/g.